Inventory of Slums with Remote Sensing Methodology as A Step to Educate A Sustainable City (Case Study of Mapping Slums in The City of Bandung) - Sijabat, Krisna Ramita; Dharmawan, Irwan Ary; Arief, Mochamad Candra Wirawan (Green Publisher Indonesia, 2025)
Urban slums remain a significant challenge in Indonesia, exacerbated by rapid population growth and inadequate local government intervention. Remote sensing technologies offer high accuracy in mapping these areas, yet a lack of community engagement and knowledge hinders their effective application. This study aims to explore the integration of remote sensing applications with community engagement strategies to enhance urban planning and development in densely populated slum areas. The research employs case studies across various urban areas in Indonesia, complemented by participatory workshops with community members and local officials to gather insights and develop a participatory framework. The study identifies barriers to stakeholder engagement and highlights the potential of combining remote sensing data with local knowledge to create actionable urban development plans. The findings contribute to sustainable urban development discourse by providing guidelines for local governments on leveraging remote sensing data while actively involving communities, ultimately improving urban planning outcomes in Indonesia.